Machinery Hall, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, ca. 1911 - Peterson, Alvin A. (1911)
Handwritten on verso: Engineering Building, UW. Former Machinery Hall, A.Y.P.E. Machinery Hall was used as the University of Washington Engineering Building until it was demolished in 1957. PH Coll 778.7 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number